Blockbuster Remakes - Constantine Verevis (Akademisk Kvarter, 2013)
Like the term “blockbuster,” the phrase “blockbuster remake” can mean different things. Typically, blockbuster remake is an industrial term, one that refers to the production of large-scale movies adapted from previously filmed properties. In this definition, modest (cult) properties – such as, Planet of the Apes (1968, 2001), King Kong (1933, 1976, 2005), and War of the Worlds (1954, 2005) – are revived through massive production budgets as cultural juggernauts, with strong marketing campaigns and merchandising tie-ins. Less typical is a description that accounts for the way in which a blockbuster movie is itself remade: that is, a definition in which a blockbuster becomes the cornerstone for the entire architecture of a blockbuster cycle. This article explores the idea of a blockbuster remake, and blockbuster initiated cycle, in and through a case study of the prototype of all modern blockbusters: Steven Spielberg’s Jaws (1975). Specifically, the article interrogates the way in which “Bruce,” the great white shark of Jaws, initiated a rogue animal cycle consisting in the first instance of the Jaws franchise – Jaws 2 (1978), Jaws 3-D (1983) and Jaws 4: The Revenge (1987) – and also a series of replicas that included Grizzly (1976), Orca (1977), and Piranha (1978).